2018
DOI: 10.2147/ott.s148670
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of COX-2 inhibitors for advanced non-small-cell lung cancer with chemotherapy: a meta-analysis

Abstract: BackgroundThe study of cyclooxygenase-2 (COX-2) inhibitors is now mired in controversy. We performed a meta-analysis to assess the efficacy and safety profile of COX-2 inhibitors in patients with advanced non-small-cell lung cancer (NSCLC).Patients and methodsA literature search of PubMed, EMBASE, the Cochrane Central databases, and ClinicalTrials.gov, up until March 26, 2017, identified relevant randomized controlled trials. Data analysis was performed using Stata 12.0.ResultsSix eligible trials (1,794 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 28 publications
0
45
1
Order By: Relevance
“…Induction of COX2 in NSCLC occurred through both the extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 pathways [30]. COX2 has been already proved a critical clinical marker for poor prognosis in lung, colorectal, gastric, head and neck cancers [24][25][26][27][28][29]. The serum level of COX2 was also validated as a biomarker for EGFR mutation, response for EGFR TKIs, and progression-free survival in LC patients [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of COX2 in NSCLC occurred through both the extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 pathways [30]. COX2 has been already proved a critical clinical marker for poor prognosis in lung, colorectal, gastric, head and neck cancers [24][25][26][27][28][29]. The serum level of COX2 was also validated as a biomarker for EGFR mutation, response for EGFR TKIs, and progression-free survival in LC patients [65].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, inhibition of COX-2 limits the production of prostaglandins, which are known to stimulate cell proliferation, induce invasiveness and mediate angiogenesis [30]. Targeting COX2 proved acceptable strategy to control lung and other malignancies [28][29][30][31][32]. Earlier in 2005, Beauchamp et al identified OC as the non-steroidal anti-inflammatory drug (NSAID) ibuprofen-like active ingredient in EVOO [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis assessed the efficacy of COX-2 inhibitors (celecoxib, rofecoxib, or apricoxib) in combination with chemotherapy in advanced NSCLC patients. 29 The results of this study showed that COX-2 inhibitors combined with first-line chemotherapy significantly improved the overall response rate (ORR) (risk ratio [RR] =1.27, 95% CI =1.07–1.50), but subgroup analysis including only 4 studies showed that celecoxib plus chemotherapy yielded no significant difference in patients with advanced NSCLC (RR =1.18, 95% CI =0.98–1.42, I 2 =0.0%, P =0.562). Additionally, this study reported that COX-2 inhibitors with chemotherapy led to higher incidences of cardiovascular events (RR =2.39, 95% CI =1.06–5.42).…”
Section: Introductionmentioning
confidence: 99%
“…repressed apoptosis, promoted tumor-cell invasion and enhanced angiogenesis in tumor cells, whereas the relevant mechanisms have not all been elucidated. Besides, higher COX-2 levels have been reported to overexpress in almost all NSCLC precursor lesions leading to a worse overall survival rate [13][14][15][16][17][18][19][20][21]. Although COX-1 has been considered not to be involved in carcinogenesis due to its homeostatic cell and tissue functions, there are many reports showing the connection between the increased levels of COX-1 and cancer pathophysiology [22][23][24][25].…”
mentioning
confidence: 99%